Implementasi Nilai - Nilai Pancasila dalam Kehidupan di Era Globalisasi - Aini Shifana Savitri; Dinie Anggraeni Dewi (Universitas PGRI Adi Buana Surabaya, 2021)
The purpose of this study is to provide an understanding of the implementation of Pancasila values in the midst of the influence of globalization that has been forgotten by some people due to the erosion of globalization. In answering the problem. This research method uses a qualitative approach through descriptive methods. The results show that many Indonesian people do not apply the values of Pancasila in their daily life and social life in this era of globalization, even some of them have forgotten the values contained in Pancasila as the way of life of the Indonesian people. Pancasila is a value system which is one unit and cannot be separated. Thus, Pancasila can become a great moral force if the overall values of Pancasila are used as a moral foundation and are applied in the life of the nation and state.